Tensions in the Triangle: Monetary Plurality between Institutional Integration, Competition and Complementarity - Blanc, Jerome (Evolutionary and Institutional Economics Review, 2018)
This text aims at accounting for the plurality of money by emphasizing the delicate and evolving balance of the legal monetary systems and the continued existence of moneys that stay outside, though their continuation is subjected to chronic difficulties. It uses Polanyian concepts to take the wide and increasing variety of money into account and mobilizes criteria able to analyse the variety of links between them. It proposes a framework based on the representation of a "plurality triangle" with institutional integration, complementarity and competition, and it analyses the positioning of moneys in this framework as well as tensions that may generate shifts in their positioning.
Keywords: current heterodox approaches: historical; evolutionary; institutional; monetary systems; money

‘Our world was made by nature’: constructions of spontaneous order - Dale, Gareth (Globalizations, 2018)
This article explores the concepts of spontaneity and spontaneous order, in particular their deployment by Friedrich Hayek and Karl Polanyi. Although in many respects these thinkers were poles apart, the article identifies a point of convergence. They both mobilize the concept of spontaneity in a manner that naturalizes a particular social process: for Hayek, the market economy, for Polanyi, society’s protective movement that arises in reaction against the market economy. To contextualize the uses of spontaneity by Hayek and Polanyi, I trace its evolution, with reference to Leibniz, Mandeville, and the thinkers of the Scottish Enlightenment. Having sketched the ways in which earlier thinkers understood spontaneity, I turn finally to Hayek and Polanyi. I argue that their invocations of spontaneity and spontaneous order contribute to a downplaying of relations of domination and exploitation. While Hayek sees the market system as the exemplar of spontaneous order, for Polanyi, the concept of spontaneity underpins his belief that the protective countermovement is a ‘natural’ reaction to the evils of market society; as such, power relations pass beneath the radar.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; HAYEK, Salma, 1968-; POLANYI, Michael, 1891-1976; social order; socialism; spontaneity; spontaneity (philosophy); spontaneous order

"Race" and the upsurge of antagonistic popular movements in Sweden - Schierup, Carl-Ulrik; Ålund, Aleksandra; Neergaard, Anders (Ethnic & Racial Studies, 2018)
Across a crisis-stricken Europe battles rage for post-neoliberal hegemony, with "race" and "austerity" as central signifiers. One of the places where the frontlines are most pregnant is Sweden; long perceived as a role model for its welfare state, cultural equity and social equality. Sweden is, however, facing social conflicts following in the tracks of a deep transformation in terms of welfare cuts, racialization and growing social polarization, targeting in particular a disadvantaged migrant and post-migrant population. On that background, the paper focuses on the upsurge of mutually antagonistic popular movements - "racist" and "anti-racist". We use Sweden as an exemplary case of Europe's present Polanyian moment, reminiscent of the 1930s. Yet, current upheavals expound, the authors claim, a different configuration of crisis and racism as well as a dissimilar utopia for the imagineering of nation and community.
Keywords: Europe; Sweden; ethnic studies; hostility; immigration opponents; migration; neoliberalism; new right (politics); populism; race; racism; social class; social movements; sociology

Globalization and Business Regulation - Djelic, Marie-Laure; Quack, Sigrid (Annual Review of Sociology, 2018)
In the twenty-first century, global business regulation has come of age. In this article, we review the literature on globalization and business regulation from the angle of transnational governance, a recently evolving interdisciplinary field of research. Despite the multiplicity and plurality of regulatory platforms and products that have emerged over time, we identify common patterns of field structuration and parallel trajectories. We argue that a major trend, both in practice and in scholarly work, is a move away from an idealized convergence around a set of unified global rules; instead, our conceptualizations and our practices of transnational business regulation increasingly demonstrate a concern for the adaptability of transnational rules to resilient and resistant contextual specificities. Another important trend, both in practice and in scholarly fields, is a growing focus on the complex dynamics between rule making on the one hand and rule implementation and monitoring on the other.
Keywords: POLANYI, Karl, 1886-1964; business regulation; globalization; governance; market ideology; neoliberalism; soft law; transnational; value chains

The economic shift and beyond: Care as a contested terrain in contemporary capitalism - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Current Sociology, 2018)
This article argues that we are witnessing a fundamental transformation of capitalism. Under the auspices of an economic shift, social reproduction and constituent care and care work are undergoing a process of reorganization. The first part draws on Karl Polanyi’s analysis of the relation between market and society and on contemporary revisions of his approach. Referring to core arguments from his perspective on the market society it identifies processes of commodification, marketization and quasi-marketization, which we can understand as an economic shift driving the development in the field of care and care work. The second part refers to empirical studies in Austria and Germany and reflects in terms of a Polanyian double movement on how far care and care work – in the case of elder and child care and, more precisely, home care agencies, residential care communities and the social investment state – have become a contested terrain. The third part, the conclusion, points out how tendencies like the economic shift touch care and care work.
Keywords: Giro económico; Virage économique; agence de soins à domicile; agencias de atención a domicilio; atención a los mayores y la infancia; capitalism; care work; communautés de soin; comunidades de atención; corporate reorganizations; doble movimiento; double movement; doublé mouvement; economic shift; elder and child care; home care agencies; inversión social; investissement social; reproducción social; reproduction sociale; residential care communities and social investment; social reproduction; social services; socioeconomics; soin aux personnes âgées et à l’enfance

Reconstructing Polanyi? - Levien, Michael (Development & Change, 2018)
Most people read Karl Polanyi today because his critique of laissez faire capitalism seems remarkably applicable to our neoliberal times. Although his late work on ancient and ‘archaic’ economies has enjoyed a consistent specialist readership, Polanyi is best known today for his 1944 magnum opus, The Great Transformation (henceforth GT). Covering a large sweep of mostly European history, the GT seeks to show that the attempt to create a ‘self-regulating market’ was a radical and recent departure from all preexisting economies; that this effort to ‘disembed’ the market from society required a great deal of state planning and force; and that the commodification of the ‘fictitious commodities’ land, labour and money was so socially destructive that it generated countermovements that demanded, and in some measure achieved, social protection. Polanyi termed this whole cycle of disembedding and re-embedding the market the ‘double movement’, and tried to show that it was the underlying cause of the great depression, fascism and two world wars. Given the relentless march of commodification in the neoliberal period and the variety of political responses this has generated (from both the left and far right), many people have been drawn to the idea that we are living through another double movement.
Keywords: DALE, Gareth; POLANYI, Karl, 1886-1964; Reconstructing Polanyi: Excavation & Critique (Book); book review; double movement; nonfiction

Capitalism goes care: Elder and child care between market, state, profession, and family and questions of justice and inequality - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Equality, Diversity & Inclusion, 2018)
The starting point of the paper is the meteoric rise of care and care work upon the societal and sociological agenda. Referring to Polanyi, the authors argue that this is the manifestation of a new phase of capitalist societalisation (Vergesellschaftung) of social reproduction in the form of an economic shift. The purpose of this paper is to discuss the societal organisation of care and care work and questions of inequality and justice.Design/methodology/approach The first part of the paper illustrates some facets of the economic shift in the field of care and care work. The second part reconstructs the societal organisation of care and care work in the private sector, state, third sector and private households from the mid-twentieth century in the context of questions of inequality and justice. The third part draws on the institutional logics perspective and French pragmatic sociology and the own case studies on home care agencies (HCA), residential care communities (RCC) and early child care (ECC) in Austria and Germany and shows how conflicting demands give rise to new questions of justice. The paper ends with a short conclusion.Findings The paper shows how the commodification and de-commodification of care and care work have changed over time and how the economic shift – illustrated in the case of HCA, RCC and ECC – is accompanied by conflicting demands and questions of justice.Originality/value A Polanyian perspective on the relation between market and society is combined with the neo-institutionalist and pragmatic idea that orientations rooted in the “logics” of the market, the state, the family and the profession influence how conflicting demands in elder and child care are dealt with and how questions of inequality and justice arise.
Keywords: capitalism; care work; caring communities and social investment; community health services; countermovement; decommodification; economic systems; elder and child care; home care agencies; home care services; social justice; social reproduction

Beyond Double Movement and Re-regulation: Polanyi, the Organized Denial of Money Politics, and the Promise of Democratization - Feinig, Jakob (Sociological Theory, 2018)
Although Karl Polanyi is best known for his theorization of market regulation and the double movement, democratizing the economic was one of his core concerns. He believed societies need to bring labor, land, and money under collective oversight to displace the logic of market fundamentalism with the logic of human needs. In this article, the author draws on Polanyi’s vocabulary to shed light on the denial of money politics and the possibility of democratization. The author illustrates these dynamics through an analysis of long-term dynamics of (de)politicization in British colonial America and the United States through the 1930s. The author developed this approach hoping that it can contribute to nudging public debates beyond regulation and monetary policy techniques and toward popular involvement and knowledge.
Keywords: Polanyi; democratization; depoliticization; double movement; gold standard; money; social theory; sociology

Discursive Synergies for a ‘Great Transformation’ Towards Sustainability: Pragmatic Contributions to a Necessary Dialogue Between Human Development, Degrowth, and Buen Vivir - Beling, Adrián E.; Vanhulst, Julien; Demaria, Federico; Rabi, Violeta; Carballo, Ana E.; Pelenc, Jérôme (Ecological Economics, 2018)
There is a growing awareness that a whole-societal “Great Transformation” of Polanyian scale is needed to bring global developmental trajectories in line with ecological imperatives. The mainstream Sustainable Development discourse, however, insists in upholding the myth of compatibility of current growth-based trajectories with biophysical planetary boundaries. This article explores potentially fertile complementarities among trendy discourses challenging conventional notions of (un)sustainable development – Human Development, Degrowth, and Buen Vivir – and outlines pathways for their realization. Human Development presents relative transformative strengths in political terms, while Degrowth holds keys to unlocking unsustainable material-structural entrenchments of contemporary socio-economic arrangements, and Buen Vivir offers a space of cultural alterity and critique of the Euro-Atlantic cultural constellation. The weaknesses or blind spots (‘Achilles heels’) of each discourse can be compensated through the strengths of the other ones, creating a dialogical virtuous circle that would open pathways towards a global new “Great Transformation”. As one of the main existing platforms for pluralist and strong-sustainability discussions, Ecological Economics is in a privileged position to deliberately foster such strategic discursive dialogue. A pathway towards such dialogue is illuminated through a model identifying and articulating key discursive docking points.
Keywords: biophysics; degrowth; ecosystem services; environemntal economics; post-development; pragmatics; socio-ecological transition; strategic dialogue; sustainable development; transformation discourses

The agrifood question and rural development dynamics in Brazil and China: towards a protective ‘countermovement’ - Escher, Fabiano; Schneider, Sergio; Ye, Jingzhong (Globalizations, 2018)
This paper explores some features of the development paths taken by Brazil and China (two member countries of the BRICS grouping) in the current context of the crisis of neoliberal globalization and transformation of the political and economic world order. The authors use Polanyi’s ‘double movement’ thesis to argue that newly emerging rural development (RD) dynamics in China and Brazil are part of a protective ‘countermovement’, driven by actors and institutions responding to the contradictions of the concentration and internationalization of agrifood systems. However, thedirectionand scope of these countermovements are still open; their transformative potential should be viewed in Gramsci’s terms as a struggle for hegemony the outcome of which depends on the concrete ‘balance of social forces’. First, the paper characterizes the impacts of China’s rise on Brazil’s development, which subsequently found its economy under threat of reprimarization and deindustrialization. The paper then sketches some stylized facts of production and consumption within the Brazil–China soy–meat complex, a key element of the current global food regime, with a focus on corporate control of the soy–meat value chain, and its negative consequences. Finally, the paper identifies the key roles that actors and institutions linked to peasants and family farmers are playing in the RD dynamics of each country. Although China and Brazil represent two very different realities, the comparison shows that critical rural and agrifood issues are indeed moving onto the centre stage of the contemporary ‘double movement’.
Keywords: Brazil; Brazil–China soy–meat complex; China; deindustrialization; double movement; farming practices; food industry; globalization; production–consumption relations; rural development; rural policies

Polanyi's Economic Embeddedness, Countermovement, and Republican Political Economy - Escandell, Bru Laín (Ethics, Politics & Society, 2018)
The aim of this article is to contend that Karl Polanyi's work bears significant coincidences with the republican tradition of thought. The first of them is one of a methodological or epistemological kind, and it consists of the use of a very
Keywords: countermovement; embeddedness; political economy; political economy and history; political philosophy; republicanism

Reconfiguring the social and solidarity economy in a Danish/Nordic welfare context - Hulgård, Lars; Andersen, Linda Lundgaard (3rd EMES-Polanyi International Seminar. Welfare societies in transition. Polanyi revisited through the lens of welfare state, social democracy and solidarity economy, 2018)
When looking at definitions and understandings of the social and solidarity economy, one issue stands out as particularly significant. The issue of how it links to organizational (micro and meso level dimensions) and societal specificities. Whereas social enterprise also in the EMES ideal typical version (Borzaga & Defourny, 2001) is only indirectly linked to a Polanyian framework (Gardin, 2006), the notion of solidarity economy can hardly be understood at an elaborate level without reference to the Polanyian framework of plurality. Accordingly, in this paper we will first highlight the difference between adopting a social economy and a solidarity economy approach to social enterprise and social entrepreneurship. Within the framework of a social economy perspective, social enterprise is first defined through a set of organizational criteria leaving the relation to the broader and deeper issues of economy and democracy open. As a contrast to this, solidar-ity economy links the organizational dimension of a particular social enterprise to the broader political and economic framework of the particular society (Laville, 2010: 230 ff.). Secondly, we will present and discuss two specific social enterprises that both re-flects the diversity of social enterprise and social entrepreneurial initiatives in a Danish welfare context and provide important insights for developing theories on solidarity economy. The two initiatives differ in shape, space/geography and organizational struc-ture but are important examples of pluralism in a Danish welfare context (Andersen, 2015). Roskilde Festival and Skovgård Hotel share a number of features that place them as interesting agents of solidarity economy. They both display a differentiated activity portfolio of business; public and civil character and they display a differentiated profile of reciprocity, redistribution and democracy that place them as influential in local, regional and national/international contexts. Finally, in the concluding section we discuss how an analysis based upon solidari-ty economy differ from one based solely upon a social economy perspective, and second-ly some future perspectives for the continued evolution of the Danish/Scandinavian wel-fare model.
Keywords: Denmark; plurality; social economy; social enterprise; social entrepreneurship; solidarity economy

The social aftermath of economic disaster: Karl Polanyi, counter-movements in action, and the Greek crisis - Kentikelenis, Alexander E. (Socio-Economic Review, 2018)
The economic crisis in Greece resulted in high unemployment and the dismantlement of social protection policies. How does society respond to the collapse of both welfare-state and market mechanisms? I examine these issues through the study of one working class community in Athens over 2012-13. Since the onset of the crisis, my informants experienced a simultaneous drop in living standards, loss of social status, and debasement of their symbolic construction of reality. To respond to these pressures, they relied on a combination of material survival strategies, the reconfiguration of social resources, and the reconstruction of cultural imaginaries. To explain these findings, the article draws on Karl Polanyi's analysis of countermovements to marketization and commodification. I argue in favour of augmenting the definition of countermovements to capture local-level responses, emphasising cultural aspects of social protection, and tracing the micro-foundations of countermovements that are nonetheless shaped by the macro-institutional context shaping action. This reading of Polanyi's work seeks to integrate many moving--and potentially contradictory--parts into a holistic analysis of societal responses to rapid and radical socioeconomic change.
Keywords: Greece; capitalist systems: political economy; countermovement; economic crisis (2008); financial crises; history of economic thought: individuals; national government expenditures and welfare programs